THE CONTROL SYSTEM DESIGN ON TACTICAL GROUND VEHICLE (TGV) FOR AKSUS TEAM PASKHAS COMMAND BATTALYON - Sahiri, Erpan; Zaini, Zaini (JOURNAL ASRO, 2024)
The Paskhas Command Battalion is the implementing unit of the Korpaskhas whose main task is to carry out operations for the seizure and defense of TNI AU strategic objects in military operations. In carrying out its duties, there is a PDR Team that carries out indoor combat tasks. However, in practice, the PDR Team still lacks data that will be used in the battle. So we need a tool that can present visual data in the room and can paralyze the enemy without having direct contact with the PDR Team and can destroy vital enemy objects to support the main troops. Therefore, it is necessary to make a supporting tool in the form of a Tactical Ground Vehicle (TGV) with remote control. By using a design method that unifies several supporting components both in mechanical and electrical systems, hardware and software as well as control systems. The control system uses wireless with a transmitter on the remote control that is integrated with the receiver at a frequency of 2.4 GHz. Utilizing a DC Brushed motor as a driver and an ESC (Electronic Speed Control) as a movement controller. Equipped with an FPV camera with a frequency of 5.8 GHz so that it can find out visual data in the room through the display screen, as well as a weapon mechanical system and weapon trigger suppression and detonator trigger that utilizes a servo motor connected to the receiver. Based on the results of the design and testing that has been carried out so that it can be used and functions properly with a success rate of 89%.Keywords: Aksus Team, Commando Battalion, Paskhas, Tactical Ground Vehicle.